Thinking in Systems: A Primer - Meadows, Donella H. (Chelsea Green Publishing, 2008)
In the years following her role as the lead author of the internationa l bestseller, Limits to Growth—the first book to show the consequences of unchecked growth on a finite planet— Donella Meadows remained a pi oneer of environmental and social analysis until her untimely death in 2001.Thinking in Systems, is a concise and crucial book offering insi ght for problem solving on scales ranging from the personal to the glo bal. Edited by the Sustainability Institute’s Diana Wright, this essen tial primer brings systems thinking out of the realm of computers and equations and into the tangible world, showing readers how to develop the systems-thinking skills that thought leaders across the globe cons ider critical for 21st-century life.Some of the biggest problems facin g the world—war, hunger, poverty, and environmental degradation—are es sentially system failures. They cannot be solved by fixing one piece i n isolation from the others, because even seemingly minor details have enormous power to undermine the best efforts of too-narrow thinking.W hile readers will learn the conceptual tools and methods of systems th inking, the heart of the book is grander than methodology. Donella Mea dows was known as much for nurturing positive outcomes as she was for delving into the science behind global dilemmas. She reminds readers t o pay attention to what is important, not just what is quantifiable, t o stay humble, and to stay a learner.In a world growing ever more comp licated, crowded, and interdependent, Thinking in Systems helps reader s avoid confusion and helplessness, the first step toward finding proa ctive and effective solutions.